Given $\begin{bmatrix} 1 &-1 \\ -1 & 1 \end{bmatrix}$, L.H.S. $A^2 = \begin{bmatrix} 1 &-1 \\ -1 & 1 \end{bmatrix} \begin{bmatrix} 1 &-1 \\ -1 & 1 \end{bmatrix}$
$\Rightarrow$ L.H.S. $ A^2 = \begin{bmatrix} 2 &-2 \\ -2 & 2 \end{bmatrix} = 2 \begin{bmatrix} 1 &-1 \\ -1 & 1 \end{bmatrix}$
R.H.S. $ = k A = k \begin{bmatrix} 1 &-1 \\ -1 & 1 \end{bmatrix}$
Since L.H.S. = R.H.S., we can see that $2 \begin{bmatrix} 1 &-1 \\ -1 & 1 \end{bmatrix} = k \begin{bmatrix} 1 &-1 \\ -1 & 1 \end{bmatrix} \rightarrow k = 2$